Finite element analysis of bolted joints - Soleh Ihsan Abd Jameel (Nanyang Technological University, 2020)
This project aims to investigate how the applied load is shared by different bolts in a bolted joint. Theoretical methods of analyses exist for this purpose. However, they do not take into account the effects of clearance between the bolt and the hole. This project will also study the effects of clearance on the sharing of applied load by different bolts. The Finite Element Analysis software, ANSYS APDL, is used for this purpose. The effect of pretension and friction is not included in this analysis. A bolted joint (with 4 bolts) under eccentric loading is analysed in this report. The bolted joint is modelled as a 2-Dimensional (2D) problem using Plane 183 element of ANSYS APDL. The contact between the bolt and the hole is modelled using contact elements. The problem is solved using geometric non-linear option of ANSYS APDL. An initial study had established that an increase of 3 orders of magnitude to the Young’s Modulus to the design along with a decrease in 3 orders of magnitude to the input displacements, had resulted to the consistency between the simulated and theoretical results. There was only a slight and insignificant deviation of a maximum percentage of 0.1%. Thus, establishing that the theoretical method that was employed had assumed conditions of a rigid bodies, with zero clearance. Subsequently, another study was done to investigate the effects of clearance in a rigid body setup. A series of clearance ranging from 0% to 10% was defined and a constant input load was applied. Results show that load held by each bolt changes as the clearance increased. A notable deviation of resultant forces and thus, the resultant angles were recorded; when compared against the findings made via theoretical methods. This concludes that the magnitude and distribution of resultant forces held at each bolt is dependent on the level of clearance introduced.